The secret hour - Westerfeld, Scott (New York : Eos, 2004)
Upon moving to Bixby, Oklahoma, fifteen-year-old Jessica Day learns that she is one of a group of people who have special abilities that help them fight ancient creatures living in an hour hidden at midnight; creatures that seem determined to destroy Jess.
740
Accelerated Reader AR
Keywords: Psychic ability -- Juvenile fiction; Science fiction; Psychic ability -- Fiction